From organizing to organizations: a typological scale of human relations management outside the legal world. Issue 2 (14th May 2020) - Neumann, Martin
Abstract : Purpose: The article examines strategies of human resource management in the absence of institutional hedging by norm-enforcing institutions such as a state monopoly of violence by using case studies of criminal organizations. This condition provides a test-bed for studying the effects of human relations management strategies on organizational performance. Design/methodology/approach: For this purpose, a case study methodology is applied. Three cases are selected to build a scale from complete plasticity of an undifferentiated network via a status differentiated gang to a hierarchical organization that provides social positions. The case studies are analysed by qualitative content analysis, network analysis and agent-based simulation. Findings: An undifferentiated network based on informal trust lacks mechanisms for conflict resolution. This is a highly vulnerable organizational structure. While a status differentiated gang is more resilient towards internal conflicts, its activities remain dependent on individually accumulated social capital. This organizational structure is not resilient over generations of actors. A hierarchical organization provides highest degree of structural resilience up to a level of a system of self-organized criticality. Originality/value: The study of human relations management outside the legal world provides insights into the basic mechanisms and functional effects of organizational activity.